Gambaran Tingkat Konsumsi Energi Protein, Pengetahuan, Aktivitas Fisik, Body Image Terhadap Risiko Kekurangan Energi Kronis Remaja Putri SMK Bina Cipta Palembang - Dinda Irawati; Sartono Sartono; Hana Yuniarti; Devy Kartika Sari (JGK:Jurnal Gizi dan Kesehatan, 2021)
Background : Chronic energi deficiency is a situation which is caused by lack of energy and protein supply for the long time, even years, the indication is the circle size of upper arm is less than 23,5 cm. Chronic energi deficiency can be influenced by some factors, direct and indirect factor. Direct factor has correlation with food supply or consumption way, and infection. Whereas indirect factor has correlation with nutrient utility obstacle, matter of economics, knowledge, education, food product less than need, and body activity. The purpose of this research is to get description of energy consumption level, protein, knowledge, body activity body image for girl students at Bina Cipta Vacational School Palembang. Methods : The kinds of research is diskriptif with crosssectional concept. This research involve 100 students, and use 36 students as sample. Chronic energi deficiency data is taken from measurement of upper arm circle size tape, energy consumption level, protein, knowing, body activity, and body image from direct interview by using questioner. Data is analyzed by unvariat in single table and bivariat in crosstable. Results : Show as that students have chronic energi deficiency are 72,2%, most of energy consumption level is not good enough (72,2%), protein consumption level is not good (52,8%), knowledge is not good (66,7%), heavy body activity is 86,1%, body image is not satisfied 72,2%. Conclusion : Consumption of energi, protein and lack of knowledge have a tendency to chronic energi deficiency, while physical activity and body image do not have a tendency to experience chronic energi deficiency.